Periodic electrochemical oscillations at a solid-solid electrode - Majoni, Stefan; Janek, Jürgen; Justus Liebig University Giessen (My University, 1996)
During the anodic dissolution of a silver electrode in the transference cell Ag¦alpha-AgI¦Ag, periodic changes of the anodic overvoltage have been observed under galvanostatic conditions. The conditions for the occurrence of these electrochemical oscillations are described. We compare the observed behaviour with similar phenomena at passivating metal electrodes in liquid electrolytes.
Keywords: Interface; Electrochemical oscillations; Solid electrolyte; alpha-AgI; ddc:540